When Maintaining Relationships and Social Connectivity Matter: The Case of New Zealand Midwives and COVID-19 - Crowther, Susan; Maude, Robyn; Bradford, Billie; Austin, Diana; Gilkison, Andrea; McAra-Couper, Judith; Krisjanous, Jayne (Frontiers in Sociology, 2021)
New Zealand’s response to COVID-19 was go hard and go early into Level 4 lockdown on 25th March 2020. This rapid response has resulted in low rates of infection and deaths. For New Zealand midwives, the sudden changes to how they work with women and families during pregnancy, birth and postnatally, especially in the community, required unprecedented innovation and adaptation. The volume of information coming from many different sources, and the speed with which it was changing and updating, added further stress to the delivery of a midwifery model of care underpinned by partnership, collaboration, informed choice, safety and relational continuity. Despite the uncertainties, midwives continued their care for women and their families across all settings. In the rapidly changing landscape of the pandemic, news media provided a real time account of midwives’ and families’ challenges and experiences. This article provides background and discussion of these events and reports on a content analysis of media reporting the impact on the maternity system in New Zealand during the initial surge of the COVID-19 pandemic. We found that the New Zealand midwife was a major influencer and initiator for relational care to occur uninterrupted at the frontline throughout the COVID-19 lockdown, despite the personal risk. The initial 5-week lockdown in March 2020 involved stringent restrictions requiring all New Zealanders, other than essential workers such as midwives, to remain at home. Midwives kept women, their families and communities central to the conversation throughout lockdown whilst juggling their concerns about keeping themselves and their own families safe. Insights gained from the media analysis suggest that despite the significant stress and upheaval experienced by midwives and wāhine/women, relational continuity facilitates quality and consistent care that honors women’s choices and cultural needs even during situations of national crisis.